Evidence-based tick acaricide resistance intervention strategy in Uganda: concept and feedback of farmers and stakeholders - Patrick, Vudriko; Okwee-Acai, James; Byaruhanga, Joseph; Tayebwa, Dickson Stuart; Omara, Robert; Bukeka Muhindo, Jeanne; Lagu, Charles; Rika, Umemiya-Shirafuji; Xuenan, Xuan; Hiroshi, Suzuki (Ticks and tick-borne diseases, 2017)
The emergence of multi-acaricide resistant ticks has led to unprecedented level of acaricide failure in central and western Uganda. In the absence of a national acaricide resistance management strategy, the country’s dairy sector is threatened by upsurge of ticks and tick-borne diseases. In this study, we developed a short-to-medium-term intervention approach called Evidence-Based Acaricide Tick Control (EBATIC): Identify, Test, Intervene and Eradicate (ITIE). Furthermore, the perception of 199 farmers and extension workers, 12 key informants in four districts and 47 stakeholders in the animal industry in Uganda were assessed using semi structured questionnaires. We report that the establishment of a specialized laboratory is pivotal in identifying and testing (IT) acaricide resistant ticks for prompt intervention and eradication (IE). The laboratory test results and the farm tick control gaps identified are very important in guiding acaricide resistance management strategies such as evidence-based acaricide rotation, development and dissemination of extension materials, training of farmers and extension workers, and stakeholders’ engagement towards finding sustainable solutions. All the 47 stakeholders and 91.0% (181/199) of farmers and extension workers reported that the EBATIC approach will help in solving the tick acaricide resistance crisis in Uganda. Similarly, all the 12 key informants and 92.5 % (184/199) of the farmers and extension workers suggested that the EBATIC approach should be sustained and rolled out to other districts. The EBATIC stakeholders’ dialogue generated both short-to-medium and long-term strategies for sustainable management of tick acaricide resistance in the country. Overall, the positive feedback from farmers, district veterinarians and stakeholders in the animal industry suggest that the EBATIC approach is a useful proof-of-concept on scalable intervention pathway against tick acaricide resistance in Uganda with possibility of adoption in other African countries.